The waterbearer - Hofmeyr, Dianne (Cape Town, South Africa : Tafelberg, 2001)
When a storm capsizes their boat and kills his father, Maji, a young trader on the East Coast of Africa in the fourteenth century, is captured and taken inland to the city of Great Zimbabwe, where he discovers a talent for divining underground water.
Keywords: Coming of age -- Fiction; Water -- Fiction; Dowsing -- Fiction; Shona (African people) -- History -- 14th century -- Fiction; Great Zimbabwe (Extinct city) -- Fiction; Africa, Eastern -- History -- 14th century -- Fiction